Mean Platelet Volume and Platelet Volume Distribution Width in Canine Parvoviral Enteritis - Engelbrecht, Monique; Atkinson, Brogan; Goddard, Amelia; Pazzi, Paolo; McClure, Vanessa (Frontiers in Veterinary Science, 2021)
Bacterial translocation from the damaged intestinal tract, reported in canine parvoviral (CPV) enteritis, is thought to be responsible for the systemic inflammatory response resulting from coliform septicemia, which could ultimately progress to septic shock and death. Alterations in platelet indices, specifically mean platelet volume (MPV), is a consistent finding in critically ill people and dogs with and without sepsis. Increased MPV has been reported to be an indirect indicator of platelet activation and of bone marrow response in people and dogs with sepsis. The study aim was to compare admission MPV and platelet volume distribution width (PVDW) in dogs with CPV enteritis to that of healthy aged matched control dogs. Forty-eight dogs with CPV enteritis and 18 healthy age matched control dogs were included. CPV infection was confirmed with electron microscopy and concurrent blood-borne infections were excluded using PCR. EDTA whole blood samples were analyzed on an automated cell counter, ADVIA 2120, within 30-60 minutes from collection. There was no significant difference for platelet count between the groups. The MPV for CPV infected dogs (median: 14.0; IQR: 12.2-15.1) was significantly higher compared to controls (11.3; IQR: 10.3-13.1, P=0.002). The PVDW for CPV infected dogs (66.9; IQR: 64.2-68.8) was significantly higher compared to controls (63.3; IQR: 60.2-65.1, P<0.001). These findings suggest that significant platelet activation is present in dogs with CPV enteritis which may play a role in the disease outcome, similar to people with sepsis. Further studies are required to investigate the prognosticating ability of MPV in dogs with CPV enteritis.